Vestibular function in cases of posterior semicircular canal canalolithiasis and cupulolithiasis - Wenyan, Xu; Lifeng, Yue; Jing, Wu; Hui, Jiang (Frontiers in Neurology, 2024)
Objective To analyze and compare the vestibular function of posterior canal cupulolithiasis and canalolithiasis. Methods The results of posterior cupulolithiasis in 45 cases, posterior canalolithiasis in 122 cases and 19 healthy controls were analyzed retrospectively. Results The abnormal rates of vHIT in the canalolithiasis group and the cupulolithiasis group were 42.6 and 37.8%, respectively, both higher than those in the control group (both p < 0.05); there was no statistically significant difference between two BPPV groups (p = 0.573). The abnormal vHIT in 76.9% of the canalolithiasis cases and 82.4% of the cupulolithiasis cases showed normal gain with saccades, with no difference between the groups (p = 0.859). The lesion location of vHIT in the two groups did not show a correlation with the affected side of BPPV (both p > 0.05). 84.4% of canalolithiasis and 65.0% of cupulolithiasis had abnormal VEMP results, with no significant differences in abnormality rates or sides (both p > 0.05). Abnormal results of VEMPs did not show any correlation with side (p > 0.05). The results of pc-ca and pc-cu were both abnormal in 14 cases and 7 cases, and there was no correlation between the site and side of the injury (all p > 0.05). Conclusion The results of vHIT and VEMP in pc-cu and pc-ca were partially abnormal, but they did not show any correlation with side of BPPV. It can be considered that there are scattered vestibular peripheral organ damage in both groups.